OPTIMASI PARAMETER POTENSIAL NUKLIR BAGI REAKSI FUSI ANTAR INTI-INTI BERAT - Viska Inda Variani; Vivin Fitrya Ningsih; Muhammad Zamrun Firihu (Universitas Halu Oleo, 2017)
Research and manufacture of optimum nuclear potential parameter optimization program for fusion reactions between heavy cores has been successfully made using Wong formula approach which is supported by Borland Delphi 7.0 visual programming language. The study was conducted specifically on the 16O+70,72,74,76Ge system by varying the value of the diversity parameter (a) and setting the depth parameter value (V0) and the radius (r0) parameter of six data. The three parameters must be set so as to produce the same VB value with the reference VB value. The resulting cross-sectional value of each input data has a different level of accuracy for the energy above VB. The results of cross-sectional calculations are then compared with the experimental results data. The Chi Square values of each cross-sectional data are interpolated with the input value a to produce a parabolic graph. The minimum peak of the graph represents an optimum value with the lowest Chi Square that can be used to determine the cross-sectional value of the fusion reaction closest to the experimental data. Keywords: nuclear fusion reaction, Wong formula, cross-reaction, heavy core, Chi Square, interpolation.